Editorial for the Special Issue: Colistin Resistance—The Need for a One Health Approach - Fabrizio Bertelloni; Barbara Turchi (Antibiotics, 2022)
Colistin is an “old” antimicrobial belonging to the class of polymyxins, initially discovered in 1947 [...]